2021
DOI: 10.1080/03007995.2021.1876005
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of clinical deterioration in non-severe patients with COVID-19: a retrospective cohort study

Abstract: Objective: Coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remains pandemic with considerable morbidity and mortality around the world. The aim of this study was to identify the predictors for clinical deterioration in patients with COVID-19 who did not show clinical deterioration upon hospital admission. Methods: Two hundred fifty-seven patients with confirmed COVID-19 pneumonia admitted to Guangzhou Eighth People's Hospital between 23 January and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…To examine the association between metformin use and other outcomes, we conducted a further meta-analyses of two (33,52), five (35,38,39,41,48,49), and four (29)(30)(31)47) studies estimating the association between metformin use and risk of intubation, deterioration, and hospitalization. The pooled ORs of metformin use with intubation, deterioration, and hospitalization were 0.94 (95% CI, 0.77-1.16; I 2 = 0.0%), 2.04 (95% CI, 0.65-6.34; I 2 = 79.4%), and 0.73 (95% CI, 0.53-1.00; I 2 = 16.8%), respectively (Supplementary Figures 2-4).…”
Section: Metformin Use and Other Covid-19 Outcomesmentioning
confidence: 99%
“…To examine the association between metformin use and other outcomes, we conducted a further meta-analyses of two (33,52), five (35,38,39,41,48,49), and four (29)(30)(31)47) studies estimating the association between metformin use and risk of intubation, deterioration, and hospitalization. The pooled ORs of metformin use with intubation, deterioration, and hospitalization were 0.94 (95% CI, 0.77-1.16; I 2 = 0.0%), 2.04 (95% CI, 0.65-6.34; I 2 = 79.4%), and 0.73 (95% CI, 0.53-1.00; I 2 = 16.8%), respectively (Supplementary Figures 2-4).…”
Section: Metformin Use and Other Covid-19 Outcomesmentioning
confidence: 99%
“…Opposite to the previous findings, Yitao et al 53 concluded that metformin was associated with greater clinical deterioration (OR 3.961; 95 % CI 1.020–15.368; p = 0.047). Similarly, Gao et al 54 concluded that metformin use was related to increasing probability of severe disease during hospitalization and to a higher risk of disease progression (OR 3.964; 95 % CI 1.034–15.194; p = 0.045).…”
Section: Resultsmentioning
confidence: 65%
“…, 44. Nevertheless, we cannot ignore the studies that point out an eventual risk association with higher clinical deterioration (Yitao et al 53 ), increased risk of disease progression (Gao et al 54 ), no-association with mortality (Oh et al 18 and Cheng et al 19 ), or even greater chance of death (Singh et al 21 and Do et al 20 ). Moreover, it is important to acknowledge that the vaccination status was not evaluated.…”
Section: Discussionmentioning
confidence: 98%
“…All, except four (20.0%), of these publications were from China [ 35 , 42 , 49 , 58 ]. Severe COVID-19 was defined based on World Health Organization guidance in three (15.0%) studies [ 35 , 49 , 58 ], recommendations from international professional bodies in two (10.0%) studies [ 44 , 70 ], national guidelines in 11 (55.0%) studies [ 38 , 42 , 46 , 47 , 51 , 53 , 56 , 57 , 73 , 74 , 76 ], and institutional policy in four (20.0%) studies [ 54 , 55 , 75 , 77 ]. Only three (15.0%) studies were considered high quality [ 42 , 54 , 58 ].…”
Section: Resultsmentioning
confidence: 99%